Mutational landscape and clonal architecture in grade II and III gliomas - Suzuki, Hiromichi; Aoki, Kosuke; Chiba, Kenichi; Sato, Yusuke; Shiozawa, Yusuke; Shiraishi, Yuichi; Shimamura, Teppei; Niida, Atsushi; Motomura, Kazuya; Ohka, Fumiharu; Yamamoto, Takashi; Tanahashi, Kuniaki; et al. (Nature genetics, 2015)
Seishi Ogawa, Atsushi Natsume and colleagues report analyses of large sets of sequence data of grade II and III gliomas. They find three distinct subtypes of grade II and III gliomas characterized by discrete mutation profiles and distinct clinical behaviors. Grade II and III gliomas are generally slowly progressing brain cancers, many of which eventually transform into more aggressive tumors. Despite recent findings of frequent mutations in IDH1 and other genes, knowledge about their pathogenesis is still incomplete. Here, combining two large sets of high-throughput sequencing data, we delineate the entire picture of genetic alterations and affected pathways in these glioma types, with sensitive detection of driver genes. Grade II and III gliomas comprise three distinct subtypes characterized by discrete sets of mutations and distinct clinical behaviors. Mutations showed significant positive and negative correlations and a chronological hierarchy, as inferred from different allelic burdens among coexisting mutations, suggesting that there is functional interplay between the mutations that drive clonal selection. Extensive serial and multi-regional sampling analyses further supported this finding and also identified a high degree of temporal and spatial heterogeneity generated during tumor expansion and relapse, which is likely shaped by the complex but ordered processes of multiple clonal selection and evolutionary events.